FEMALE VOTER PARTICIPATION IN THE 2024 GENERAL ELECTION OF BAUBAU CITY DPRD MEMBERS - Edi Sabara; Andi Tenri; La Didi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Research purposes For analyze participation voters Woman in General Election for Members of the Baubau City Regional People's Representative Council 2024. Problems​ study focused on gaps between height level participation numeric voters Woman with quality participation political in a way substantive , representative , and its influence to taking decision public . For answer problem said , research This use references theoretical from field administration public , participation politics , gender studies , and governance democracy . Data collected through interview in-depth , observation , and documentation with involving organizer elections , voters women , and members legislative women , then analyzed in a way qualitative use technique interactive data analysis . Research results show that mechanism administrative gender responsive elections , policies affirmative , and involvement meaningful Woman in institution organizer elections capable increase participation and trust Woman towards the democratic process . Although representation women in institutions legislative Still limited in a way quantitative , its existence give contribution substantive to policy more public​ inclusive and gender responsive . Research This conclude that strengthening commitment institutional , regulatory gender and culturally sensitive inclusive organization​ is key For overcome obstacle structural and cultural as well as speed up equality political women at the level local .